2004
DOI: 10.1111/j.1745-4557.2004.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cow Milk in Buffalo “Mozzarella” by Polymerase Chain Reaction (Pcr) Assay

Abstract: The authors used a polymerase chain reaction (PCR) assay on buffalo mozzarella, a typical Italian dairy product, from the Apulia markets to evaluate the presence of cow milk and verification of the mozzarella label. The results obtained from 30 mozzarella samples demonstrated the presence of the cow genome in 22/30 samples, highlighting contamination as probable fraudulent adding of cow's milk or use of the same equipments in both working cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…However, a widespread adulterant practice found in the dairy industry is the use of a less costly type of milk instead of more expensive ones. An eminent example is the addition of cow's milk to sheep's, goat's or buffalo's milk or other dairy products that are faultily labeled "pure sheep," "pure goat," or "pure buffalo" (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…However, a widespread adulterant practice found in the dairy industry is the use of a less costly type of milk instead of more expensive ones. An eminent example is the addition of cow's milk to sheep's, goat's or buffalo's milk or other dairy products that are faultily labeled "pure sheep," "pure goat," or "pure buffalo" (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of milk by PCR amplification of DNA is based on the presence of mammalian somatic cells in the milk (Herman, 2001). Several simplex PCR procedures have been developed for species identification in milk, cheese and yogurt based on primers designed to amplify a number of mitochondrial genes: cytochrome b (cytb) (Bania, Ugorski, Polanowsk, & Adamczyk, 2001;Di Pinto, Conversano, Forte, Novello, & Tantillo, 2004;Herman, 2001), D-loop region (Maudet & Taberlet, 2001), 12S ribosomal RNA gene (Ló pezCalleja et al, 2004;Ló pez-Calleja et al, 2005), cytochrome oxidase II (Mayer, 2005), cytochrome oxidase I (Feligini et al, 2005), and nuclear encoded genes e.g. coat colour MC1R (Maudet & Taberlet, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Most research papers using the PCR technique for the estimation of undeclared additions of cow's milk give the detection limit within the range of 0.1 to 1%. Thus, the PCR method helped to detect the addition of 1% cow's milk in buffalo milk (REA et al 2001), 1.5% addition of cow's milk to mozzarella cheese (DI PINTO et al 2004), or 5% addition of cow DNA to goat's, sheep's, or buffalo's milks, and 2% addition to goat cheeses (KLOTZ & EINSPANIER 2001). PLATH et al (1997) identified 0.5% cow's milk in goat and sheep cheeses and FELIGINI et al (2005) detected 0.5% cow's milk in Italian mozzarella.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly as in the present study, Kaškaval ranked among the cheeses with the positive detection of an undeclared ingredient. DI PINTO et al (2004) analysed 30 mozzarella cheeses and the presence of cow's milk was found in 22 samples.…”
Section: Resultsmentioning
confidence: 99%